Adaptasi Siswa Baru terhadap Pelajaran IPA pada Perpindahan Pembelajaran Daring ke Pembelajaran Luring - Ayu Rischi Utami; Jumadi; Nina Khaerunnisa; Muhamad Arif Nur Rokhman (Postgraduate, University of Mataram, 2023)
This study aims to examine the adaptation of new students to science subjects in the transfer of online learning to offline learning. This research used the quantitative and qualitative approach with technique data collection through survey questionnaires and interviews. The subject of this research is new students of VIIth junior high school and Xth Senior High School which get science lessons. The survey questionnaire be distributed via google form that has been made and technique interviews were conducted by students of Xth Senior High School MAN 3 Sleman, MA Darul Qur’an, and VIIth junior high school SMP N 1 Piyungan , MTS Darul Qur’an Wahid Hasyim with 74 sample. Most new students of VIIth junior high school and Xth Senior High School is capable of adapting with their school. It is also capable of adapting in terms of communication with friends and teachers at schools. This adaptation also is a challenge to them to better understanding of the situation and the condition at their school to receive a comfort learning in school especially at science lessons. Science lessons in the learning process it takes a lot of communication, a good cooperation, and liveliness from each new students caused by science lessons there are skill process which using lab work.